Ectomycorrhizal Fungi Associated With Pinus sylvestris var. mongolica Were Altered by Soil Environments With Aging Plantation in a Semi-arid Desert - Yue Ren; Yue Ren; Yue Ren; Mishan Guo; Guodong Ding; Guodong Ding; Guodong Ding; Yue Wang (Frontiers in Environmental Science, 2022)
Pinus sylvestris var. mongolica (P. sylvestris) is a pioneer afforestation species for wind and sand fixation in northern China. However, most plantations have undergone unprecedented degradation since the early 1990s. Ectomycorrhizal (EcM) fungi are expected to be substantially related to the degradation of P. sylvestris plantations; however, the direct evidence for this remains unclear. For this purpose, we investigated variation among EcM fungal communities associated with P. sylvestris root samples of three age groups (half-mature, near-mature, and mature) in Mu Us Desert. Our results found a total of 72 EcM fungal operational taxonomic unit (OTU) belonging to Basidiomycota (63) and Ascomycota (9). The EcM fungal community is highly enriched in Rhizopogon, Tuber, Tomentella, and Inocybe, and the variations of their abundance mainly contribute to community differences. The diversity index and fungal species richness showed increasing trends toward the mature forest but did not reach a significant level (p > 0.05). The main factors that affected the dominant EcM fungal community were URE, INV, and SOC, but for the whole EcM fungal community, the effects of soil environments with plantation aging are not significant (p > 0.05). Understanding the effects of environmental factors on the structuring of the EcM fungal communities is critical to sustainable forest management in the future.